Analisis Faktor Predisposing, Enabling dan Reinforcing dengan Pelaksanaan Peran Kader Dalam Pencegahan Stunting di Wilayah Kabupaten Lombok Tengah - Nurwahidah, Nurwahidah (MARAS : Jurnal Penelitian Multidisiplin, 2025)
Nutrition problems, especially stunting in infants, can inhibit a child's development, with negative impacts that will last in the next life such as intellectual decline, susceptibility to non-communicable diseases, decreased productivity to cause poverty and the risk of giving birth to babies with low birth weight. The purpose of this study was to analyze the factors of predisposing, enabling and reinforcing by implementing the role of cadres in stunting prevention in the Central Lombok District of NTB. The design of this research is correlational analytic with cross sectional approach. Data collection using a questionnaire, data analysis with logistic regression tests at α = 0.05. The results showed that there was an influence of knowledge on the implementation of the role of cadres in stunting prevention in NTB Central Lombok District (p-value = 0.003), there was an influence of attitudes towards the role of cadres in stunting prevention in the Central Lombok District of NTB (p-value = 0.004 < α = 0.0). there is an influence of infrastructure on the implementation of the role of cadres in stunting prevention in the Central Lombok District of NTB (p-value = 0.001), there is an influence of family support for the implementation of the role of cadres in preventing stunting in the Central Lombok District of NTB (p-value = 0.001) and there is an influence of predisposing, enabling and reinforcing factors with the implementation of the role of cadres in preventing stunting in the Central Lombok Regency of NTB (p-value = 0,000). Lack of knowledge leads to the formation of negative attitudes towards efforts to prevent stunting by cadres due to lack of information. The means serves to realize the role of cadres into real behavior. Routine guidance from health workers in the form of informational and awards will certainly be a source of encouragement for cadres in carrying out their roles.